Silica@layered double hydroxide core-shell hybrid materials - Kwok, W; Crivoi, D; Chen, C; Buffet, J; O'Hare, D (Royal Society of Chemistry, 2017)
A series of silica@layered double hydroxides (SiO2@Mg2Al-CO3-AMO-LDHs) have been synthesised by in-situ precipitation of Mg2Al-CO3-LDH at room temperature in the presence of amorphous spherical silica particles (~500 nm). We have systematically investigated a number of synthetic parameters in order to evaluate their effects on the composition, morphological and physical properties of the isolated materials. Syntheses carried out at moderate stirring speeds (e.g. 500 rpm) were found to promote the formation of vertically aligned LDH platelets with respect to the silica surface. Addition rates of the metal solutions, slower than 0.43 mmol h 1, were found to create a thicker LDH shell consisting of vertically aligned LDH platelets. When the metal solutions were added rapidly (0.86 mmol h 1), we observed that for both slow and fast stirring speeds the synthesised core-shell materials had thin LDH shells and the majority of the LDH precipitated independent of the silica, forming unbound “free” LDH.